Undang-Undang Cipta Kerja: Berbaju Pancasila, Bernapas Kolonial - Fathonah, Rini; Anwar, Mashuril (UIN Jakarta, 2021)
Abstract:The influence of Western values and ideology has infiltrated Indonesia's national legal instruments through deregulations which appear to always be in favor of the investor interest groups. This can of course be seen from the various laws made to protect the interests of capital owners, one of which is Law Number 11 of 2020 concerning Job Creation (Job Creation Law). Based on the reasons for considering it, the Job Creation Law was formed to realize the goal of forming the Indonesian state government and to create a prosperous, just, and prosperous society based on Pancasila and the 1945 Constitution. However, if we look closely, the considerations for the formation of the Job Creation Law tend to be economical, not welfare.Keywords: Pancasila; Colonial; Job Creation Act